Penyelesaian Sengketa Keterbukaan Informasi Publik di Pengadilan Tata Usaha Negara - Nor Lailatul Mutfaidah; Abd. Wachid Habibullah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Openness of public information is an important principle in transparent and accountable government. Openness of information also allows citizens to understand the problems faced by the government and how proposed policies may affect their lives. This research describes the resolution of public information disclosure disputes starting from the Information Commission up to the Cassation level at the PTUN. The approach method used in this research is normative juridical research. This research explains the procedures for resolving public information disputes at the PTUN using the litigation adjudication process regulated by Law Number 14 of 2008 concerning Openness of Public Information and PERMA RI Number 2 of 2011 concerning Procedures for Resolving Public Information Disputes in Court.